2018
DOI: 10.1103/physrevfluids.3.024301
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-driven, dry granular flows over a loose bed in stationary and homogeneous conditions

Abstract: Flows involving solid particulates have been widely studied in recent years, but their dynamics are still a complex issue to model because they strongly depend on the interaction with the boundary conditions. We report on laboratory investigations regarding homogeneous and steady flows of identical particles over a loose bed in a rectangular channel. Accurate measurements were carried out through imaging techniques to estimate profiles of the mean velocity, solid concentration, and granular temperature for a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The stereoscopic imaging methods permit measurement of velocity profiles of the three components of the velocity vector (Spinewine et al ., ) and represent a development of the monocular imaging method (Capart et al ., ). They both rely on the Voronoï tessellation and on Delaunay triangulation, but, whereas the former is more complicated and needs two high speed cameras (a set up photograph in Figure ), the latter is simpler and exploits only one camera (Meninno, ; Meninno et al ., ). The main steps of these procedures are implemented in an in‐house Matlab routine and are similar.…”
Section: Methodsmentioning
confidence: 97%
“…The stereoscopic imaging methods permit measurement of velocity profiles of the three components of the velocity vector (Spinewine et al ., ) and represent a development of the monocular imaging method (Capart et al ., ). They both rely on the Voronoï tessellation and on Delaunay triangulation, but, whereas the former is more complicated and needs two high speed cameras (a set up photograph in Figure ), the latter is simpler and exploits only one camera (Meninno, ; Meninno et al ., ). The main steps of these procedures are implemented in an in‐house Matlab routine and are similar.…”
Section: Methodsmentioning
confidence: 97%
“…Grainflow dynamics in natural aeolian environments differ substantially from those observed in simulated environments. For example, in the latter, there are experimental constraints that limit the magnitude and perhaps speed of simulated grainflows, sediment sizes are often carefully constrained (Börzsönyi et al., 2008; Meninno et al., 2018), and sand surfaces groomed (Russell et al., 2019). After each grainflow, the surface is repaired before an experiment is repeated (Tischer et al., 2001), and grainflows develop in ideal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Gravity‐driven grainflows or granular flows (Russell et al., 2019) or avalanches (Sutton et al., 2013a, 2013b) are ubiquitous on the lee slopes of migrating sand dunes on Earth and elsewhere. Grainflows have been the focus of substantial laboratory research and related modeling efforts to address the fundamental physics of particle flow (Dai et al., 2020; Drake, 1990; Li et al., 2016; Meninno et al., 2018; Silbert et al., 2001); applications in manufacturing or food and pharmaceutical processing (Gray, 2001; Rao et al., 2008); the behavior of sand piles in the context of self‐organized criticality (Abate et al., 2007; Dendy & Helander, 1998; Kadanoff et al., 1989; Mosco & Vivaldi, 2020); the controls on grainflow characteristics on inclined planes (Börzsönyi et al., 2008; Meninno et al., 2018; Rendina et al., 2019; Tischer et al., 2001); or grainflows on simulated dune slopes (Allen, 1970; McDonald & Anderson, 1992, 1995). Important studies have focused on key grainflow characteristics such as critical slope angles for the initiation of movement (Börzsönyi et al., 2008; Edwards et al., 2019; McDonald & Anderson, 1992; Sutton et al., 2013b); the dynamics of flow processes (Drake, 1990); relationships between the magnitude and frequency of grainflows and sand transport rates (Sutton et al., 2013a); grainflow shapes (Cornwall, Bourke, et al., 2018; Cornwall, Jackson, et al., 2018; Ewing et al., 2017; McDonald & Anderson, 1995, 1996; Nickling et al., 2002; Nield et al., 2017; Sutton et al., 2013a; Tischer et al., 2001; P. Zhang et al., 2022); and controls on the length and speed of grainflows (Börzsönyi et al., 2008; McDonald & Anderson, 1995, 1996; Meninno et al., 2018; Tischer et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This was compared to the PIV analysis, showing a good match (2% difference). Furthermore, for channels that are wide enough compared with the grain size (W/d = 250), lateral walls have a negligible influence (Meninno et al, 2018) on average flow velocity. Considering that the ratio of channel width and particle size here (W/d ∼ 2,000) is much larger than the threshold value (W/d = 250) given by Meninno et al (2018), the observed erosion kinematics from side view are advisable.…”
Section: Observed Entrainment Kinematicsmentioning
confidence: 99%
“…Furthermore, for channels that are wide enough compared with the grain size (W/d = 250), lateral walls have a negligible influence (Meninno et al, 2018) on average flow velocity. Considering that the ratio of channel width and particle size here (W/d ∼ 2,000) is much larger than the threshold value (W/d = 250) given by Meninno et al (2018), the observed erosion kinematics from side view are advisable. Figure 6 shows the observed erosion process in the case of water repellent bed with 20% volumetric water content (test ID: R_20).…”
Section: Observed Entrainment Kinematicsmentioning
confidence: 99%